Pondok Pesantren Salaf in Java: Study of Santri Observation of Suhita’s Heart - Lisnawati, Agustin; Zuhro, Wahidah Zumrotul (Proceeding International Conference on Science and Engineering, 2020)
This article aims to reveal how the grammar or manners of a student towards Kiai and Bunyai. This article is expected to be able to be a view among the students and readers in the future regarding the moral values and rules not written in the boarding school Salaf but still implemented. The Islamic boarding school is known as a sacred place because it not only teaches academic and non-academic knowledge, but also forms characters and students in accordance with the teachings of Islam. This research uses a type of qualitative descriptive research. The subject in this study was the novel Suhita by Khilma Anis. The way the data collection is done by the researchers by reading repeatedly and writing quotes that are found in novels into books. In this article there are two focus questions, first, how the communication between the nanny boarding school towards the students of the perspective of the novel Liver Suhita. Secondly, how is the moral value or rule described by the caliphate of the novel Suhita novels concerning the Pondok Pesantren Salaf. The results of this research show, firstly, the pattern of communication between the nanny Pondok Pesantren Salaf with a students of the study novel suhita. Secondly, the students ’ obedience to the moral rules and values in Salaf pondok pesantren is a novel hati suhita.